2021
DOI: 10.1186/s40168-021-01040-x
|View full text |Cite
|
Sign up to set email alerts
|

Joint contributions of the gut microbiota and host genetics to feed efficiency in chickens

Abstract: Background Feed contributes most to livestock production costs. Improving feed efficiency is crucial to increase profitability and sustainability for animal production. Host genetics and the gut microbiota can both influence the host phenotype. However, the association between the gut microbiota and host genetics and their joint contribution to feed efficiency in chickens is largely unclear. Results Here, we examined microbial data from the duodenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 112 publications
2
72
1
1
Order By: Relevance
“…In addition to the genera we identified, Acinetobacter and Arcobacter have also been reported to be predominant in broilers with high FCR, whereas microbes such as Barnesiella and Cloacibacillus were found to be abundant in broilers with low FCR ( Singh et al, 2012 ). Wen et al (2021) have demonstrated that lower abundances of duodenal Akkermansia muciniphila and cecal Parabacteroides , and higher abundances of cecal Lactobacillus , Corynebacterium , Coprobacillus , and Slackia were interrelated to better feed efficiency. Interestingly, Akkermansia muciniphila , as a member of phylum Verrucomicrobia, was also detected in the duodenum of our experimental broilers with extreme low relative abundance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the genera we identified, Acinetobacter and Arcobacter have also been reported to be predominant in broilers with high FCR, whereas microbes such as Barnesiella and Cloacibacillus were found to be abundant in broilers with low FCR ( Singh et al, 2012 ). Wen et al (2021) have demonstrated that lower abundances of duodenal Akkermansia muciniphila and cecal Parabacteroides , and higher abundances of cecal Lactobacillus , Corynebacterium , Coprobacillus , and Slackia were interrelated to better feed efficiency. Interestingly, Akkermansia muciniphila , as a member of phylum Verrucomicrobia, was also detected in the duodenum of our experimental broilers with extreme low relative abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Longer digestion time of nutrients in the cecum allows enhanced microbial fermentation ( Rehman et al, 2007 ). Feces are easy to sample for subsequent analysis and are usually used as substitutes for intestinal microbiota ( Wen et al, 2021 ). However, the heterogeneity of digestive tract function leads to the regional differences within the intestinal microbial populations ( Martinez-Guryn et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latest years, the chicken gut metagenome and its modulatory effects on production performance, the heritability of chicken gut microbe, and the interactive regulation on feed efficiency between host genetics and gut microbiome have been well-studied ( 1 , 2 ). However, little information could be acquired about geese.…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiome is considered the host second genome, which emerged as a key determinant of many aspects including the capability of shaping developmental, physiological and reproductive phenotypes ( 5 ), the enhancement of feed digestibility and nutrient absorption throughout the digestive tract ( 2 ), and the inhibition on intestinal pathogenic bacteria ( 6 ). Further, unlike other environmental factors, the microbiomes may be transmitted between generations carrying the potentiality to alter traits beyond the limits of the host's genetics ( 7 ), and further worked on shaping the phenotypes of the progenies.…”
Section: Introductionmentioning
confidence: 99%